Study on match strategy in badminton group competition - Song, A. L.; Chen, K.; Liu, X. (Advanced Materials Research, 2011)
Scientific rational match strategy matters the result of badminton group competition, on which in-depth research has important theoretical and practical value. In this paper, a program for investigation on match strategy in badminton group competition is presented. It can provide important theoretical reference for coaches in match strategy training and its plan. And its further application can be used for quantitative analysis of atheletes` psychological pressure in competition.